Differential microRNA (miRNA) expression could explain microbial tolerance in a novel chronic peritonitis model. Issue 2 (April 2013) - Kanaan, Ziad; Barnett, Rebecca; Gardner, Sarah; Keskey, Bobby; Druen, Devin; Billeter, Adrian; Cheadle, William G
We observed persistent peritoneal bacteria despite a transient early innate immune response to intraperitoneal (IP) Klebsiella pneumoniae . Pretreatment with LPS prior to peritonitis induced a tolerant pattern of pro-inflammatory cytokine protein production over 72 h, but not at the mRNA level. MicroRNAs (miRNAs) regulate inflammatory cytokines and may explain this paradox. After pretreatment with IP LPS or saline, C57BL/6 mice were given 10 3 CFU of K. pneumoniae IP. Total RNA was isolated from peritoneal exudate cells (4 h, 24 h and 48 h following infection). mRNA and miRNA expression levels were detected and bioinformatics pathway analysis was performed, followed by measuring TNF-α, IL-1β, IL-6 and High-mobility Group Box 1 (HMBG1) protein levels. Of 88 miRNAs studied, 30 were significantly dysregulated at all time points in the LPS-pretreated group, including MiR-155, -146a, -142-3p, -299, and - 200c -132 and -21 . TNF-α, regulated by miR-155 and miR-146a, was decreased in the LPS-pretreated group at all time points ( P < 0.05), as were HMGB1, a key alarmin regulated by miR-146, -142-3p, -299 and - 200c ( P < 0.05), and IL-1β and IL-6, both regulated by miR-132 and miR-21 respectively ( P < 0.05). Specific dysregulation of miR-155, -146a, -142-3p, -299, and - 200c -132 and -21 with their corresponding effects on the TLR and NF-κB signaling pathways during inflammation, suggests a plausible mechanism for tolerance in this novel chronic model with persistent peritoneal infection.